MONEY DEMAND STABILITY IN MOROCCO AND THE EFFECTIVENESS OF MONETARY POLICY: AN ECONOMETRIC STUDY WITH THE CO-INTEGRATED VAR MODEL - EL HASSANI , Hafid; OUALI , Idriss (Revue du contrôle, de la comptabilité et de l’audit, 2022)
The main objective of this paper is to study the stability of the demand for money in Morocco and its implication on the conduct of monetary policy. Our data were extracted from the World Bank and the High Commission for Planning database and consist of annual data covering the period from 1990 to 2018. We adopt an approach based on the concept of cointegration. After studying the stationarity of the variables, the VAR econometric specification suitable for our study is that of the cointegrated VAR model. In light of the results of the empirical study on the Moroccan case, we can conclude that the currency demand function in Morocco is stable over the period studied, and the demand for M3 currency in Morocco is predictable and can be used for the effective implementation of monetary policy.